2019
DOI: 10.31629/kemudi.v4i1.1297
|View full text |Cite
|
Sign up to set email alerts
|

Reformasi Agraria Joko Widodo-Jusuf Kalla dalam Konsep dan Realita Kepemimpinan yang Fasilitatif (Facilitative Leadership)

Abstract: The focus of the discussion in this paper will examine leadership theoretically and case studies are seen as an important element in bringing stakeholders to direct them to carry out collaborative processes or what we call Facilitative Leadership. But this concept of leadership is not a traditional leadership concept that has been known. Jokowi-Jusuf Kalla's leadership contains the agenda of the Agrarian Reform which starts from the regions and villages. In the Nine Priority Agenda, also known as Nawacita, it … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
1
0
1
Order By: Relevance
“…Regarding Widodo, Ikhsan and Muhammad (2019) explained that in general, we showed that leadership plays a vital role in the collaborative planning process by resolving conflicts, imagining a vision, organizing knowledge and resources, fostering trust, persuading stakeholders to collaborate, performing tasks, and building a learning framework. Facilitative leadership seems to challenge the assumptions of strong technical mastery and decision making associated with instructional leadership.…”
Section: Crises and Leadership In Indonesiamentioning
confidence: 99%
“…Regarding Widodo, Ikhsan and Muhammad (2019) explained that in general, we showed that leadership plays a vital role in the collaborative planning process by resolving conflicts, imagining a vision, organizing knowledge and resources, fostering trust, persuading stakeholders to collaborate, performing tasks, and building a learning framework. Facilitative leadership seems to challenge the assumptions of strong technical mastery and decision making associated with instructional leadership.…”
Section: Crises and Leadership In Indonesiamentioning
confidence: 99%
“…Selain itu, pola kepemimpinan insruksional juga digunakan selama menjabat sebagai kepala madrasah dimana pola instruksional dan partisipatif (Rosintan, 2014) sebagaimana Groove menyebutnya sebagai kepemimpinan fasilitatif (Juliana Murniati, 2023), yang ditandai dengan upaya kepala sekolah lebih banyak berinteraksi dengan guru, siswa, orang tua, kolega, komunitas, lebih dari laki-laki, mendukung pembuatan keputusan konsensus, menekankan proses, mendorong perasaan harga diri, partisipasi aktif, dan berbagi kekuatan dan informasi yang membantu mengubah minat diri orang ke dalam tujuan organisasi, mempengaruhi guru untuk menggunakan metode mengajar yang lebih diinginkan dalam keseharian. Dengan kata lain, kepemimpinan dan pola tersebut merupakan fasilitator atas proses kolaboratif atau dapat disebut dengan kepemimpinan yang fasilitatif (facilitative leadership) (Khairul Ikhsan, 2019). Pola ini juga diterapkan dimana kepala sekolah berinteraksi secara aktif dengan guru, siswa juga orang tua murid dan masyarakat, sebagaimana yang diutarakan oleh Kepala Sekolah, "Selama saya menjadi kepala, saya berupaya dekat dengan semua guru dan siswa.…”
Section: Gaya Kepemimpinan Kepala Sekolah Perempuan Islam DI Mts Al-h...unclassified